Ownership Structure, Board Size, and Carbon Emission Disclosures: Empirical Evidence from ASEAN-5 Countries - Lina, Lina; Rohmah, Faizah Syifa (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2024)
This study aims to investigate the influence of institutional ownership structure and managerial ownership on corporate carbon emissions disclosure in ASEAN-5 with the size of the board of commissioners as a moderator. Large-cap companies listed on each ASEAN-5 countries stock exchange were selected as research samples. The sample companies have published sustainability reports and integrated annual reports that disclose carbon emissions between 2018 and 2022 (175 company-year observation). Using multiple linear regression analysis, this study found that institutional ownership and managerial ownership have a negative impact on carbon emissions disclosure. The role of board of commissioner size was found weakening the negative relationship between institutional ownership and managerial ownership on carbon emissions disclosure.